Research progress on green adsorption process for water pollution control applications - Opeyemi A. Oyewo; Anthony M. Muliwa; Seshibe S. Makgato; Damian C. Onwudiwe (Hybrid Advances)
Anthropogenic activities, such as domestic, agricultural, and industrial activities, are responsible for the increased water resource scarcity and pollution. However, existing water treatment techniques such as adsorption have been used successfully to control water pollution. This process is commonly employed in water treatment and among it is one of the water treatment technologies. Additionally, an increase in the hazardous chemicals in processed water due to the introduction of some chemically synthesized or commercial adsorbents suggests the need for research extension to green adsorption process. The unique properties of green adsorbent, such as adjustable particle size, excessive active sites, high chemical stability, cost-effectiveness, efficiency, bioavailability, and environmentally friendliness promote its usage. Subsequently, this study elucidated the types of green adsorbents, the advantages and limitations of the existing synthesis routes and their performances in water treatment applications. The limitation in the large-scale production of green adsorbents for real industrial applications and their reusability of spent adsorbent is also highlighted. Overall, the future development of green-based adsorbents for real industrial applications is discussed.